Self, nation, text in Salman Rushdie's Midnight's children - Kortenaar, Neil ten (McGill-Queen's University Press, 2004)
"Self, Nation, Text in Salman Rushdie's Midnight's Children is an in-depth study of one of the most important novels of the twentieth century. Neil ten Kortenaar shows that the hybridity of Rushdie's fictional India is created not by the combination of different elements to form a single whole but rather by the relationship among these elements: Rushdie's India is more self-conscious than are communal identities based on language; it is haunted by a dark twin called Pakistan; it is a nation in the way England is a nation, but is imagined against England; it mistrusts the openness of Tagore's Hindu India; and it is at once cosmopolitan and a particular subjective location. The citizen in turn is imagined in terms of the nation. Saleem Sinai's heroic identification of himself with the state is beaten out of him until at the end he sees himself as the Common Man at the mercy of the state."--Jacket